Evaluation of semen in Ethiopian Indigenous bulls (Horro bulls) - SORI, HUNDERRA; PRASAD, SHIV; ZEWDIE, EMIRU (The Indian Journal of Animal Reproduction, 2023)
Semen ejaculates (n = 38) were collected at weekly interval from three Horro bulls kept at Kaliti Artificial insemination (AI) center, Ethiopia for thirteen weeks to evaluate the ejaculate for its physico-morphqlogical and biochemical parameters. The overall mean (SE) value for volume 5.28 (0.24) ml, mass motility 3.17 (0.12), individual motility 69.36 (1 .76 %), concentration 1.34 (0.06) billions/ml, total count 7.03 (0.41 )billions/ejaculate, viable number 4.85 (0.29)billions/ejaculate, total morphologically normal number 6.64 (0.42) billions/ejaculate, live percentage 81.47 ( 1.2), morphologically normal per cent 94.1 (0.5), per cent normal acrosome 98.23 (0.33), GOT 1475.1 (69.96) U/1, GPT 150.8 (19.24) U/1, ALP 2674.3 (202.45) U/1, ACP 4503 (309.7) U/ I, total protein 7.3 (0.3) g/dl, testosterone 1.21 (0.18) ng/ml, head abnormality 1.81 (0.20) %, midpiece abnormality 2.60 (0.35) %, tail abnormality 1.50 (0.18) %, total abnormality 5.90 (0.51) %, major abnormality 3.02 (0.29) %, minor abnormalities were 2.9 (0.33 %).During the study it was found that semen of Horro bulls has very less numbers of the different types of spermatozoa morphologic abnormalities compared to semen features set for normal fertile bulls.